Analisis Fitokimia dan Analisis GCMS Ekstrak Kembang Bulan Tithonia Diversifolia (Hemsl.) A. Gray: Analisis Fitokimia Dan Analisis GC-MS Ekstrak Kembang Bulan Tithonia Diversifolia (Hemsl.) A. Gray - Dewi Rahma Fitri; Dedri Syaefei; Kartika Sari (JURNAL FARMASI DAN MAKANAN, 2025)
Extracts from plants made from simple drugs are used as active ingredients, intermediates or finished product ingredients. The extract is standardized with two parameters specific and non-specific parameters. Non-specific extract quality parameters are indirect tests related to active compounds and their pharmacological activity, but aim to ensure the quality and uniformity of the extract. Specific extract quality parameters are aspects of chemical analysis that focus on the removal and quantification of active compounds in the extract that affect its pharmacological activity. The purpose of this study was to obtain a moonflower extract that meets specific quality standards related to the content of active compounds both qualitatively and quantitatively. The research method by testing the chemical compounds contained in the moonflower extract includes phytochemical screening, GCMS analysis and phenol content and total flavonoid content. The results of the study obtained 70% ethanol extract of moonflower with a yield value of 18.19%. Organoleptically, it is reddish brown in color, with a distinctive aroma of moonflower. The results of the water content are 9.79%, ash content 11.99%, and drying loss 13.64%. Contains flavonoids, phenols and tannins. The results of GCMS analysis contain compounds Benzenetricarboxylic acid, Cyclotetrasiloxane, octamethyl, Salicic acid, diethyl bis (trimethylsilyl) ester, Cyclotetrasiloxane-octamethyl, Heptasiloxane. Total flavonoid content is 3.2 Mg / g EQ and total phenolic content is Mg / g GEA.